Adoption of Mobile Payment Technology by Consumers. (June 2014) - Garrett, Jamie Lynn; Rodermund, Robert; Anderson, NaRita; Berkowitz, Sara; Robb, Cliff A.
<x xml:space="preserve">Abstract</x> This study examined the use of mobile payments by American consumers. Using a sample of 15, 060 respondents from all 50 states and the District of Columbia, a profile of mobile payment users was developed. Respondents who were using mobile payments were more likely to be younger, male, minorities, and to have a higher than average income. Results indicated that there were strong associations between mobile payment adoption and high cost debt (payday loans, auto‐title loans, etc.), trouble with financial management (making ends meet), and credit card behavior (taking cash advances and paying over the limit fees). Results suggest that users of mobile payment technology were focused on convenience, and they might be prone to impulse spending. The potential impact of the increasing adoption of this technology is discussed.